Book review: Periglacial geomorphology, by Colin K. Ballantyne, 2018. Wiley-Blackwell, Chichester. 454 pages. Paperback: price 78.00, ISBN 9781405100069. - Strzelecki, Mateusz C. (Geologos, 2020)
Book review: Periglacial geomorphology, by Colin K. Ballantyne, 2018. Wiley-Blackwell, Chichester. 454 pages. Paperback: price 78.00, ISBN 9781405100069.